Understanding Outdoor Play Types and Their Impact on Children’s Psychosocial Well-being: A Narrative Review - Nabilah Abd Talib; Wong, Rita Mee Mee; Khairul Firdaus Ne’matullah; Lim, Seong Pek; Saturia Amiruddin; Md Rosli Ismail (Human Resource Management Academic Research Society, 2023)
Despite growing evidence of the benefits of outdoor play on children’s well-being, the amount of time children spend playing outside has decreased in recent years. Furthermore, due to current technological advancements and the recent pandemic, children are more prone to engage in indoor sedentary activities, increasing their chance of developing Childhood Psychosocial Dysfunction (CPD). The systematic narrative review is conducted to examine the various types of outdoor play and their influence on children’s psychological well-being. The Preferred Reporting Items for Systematic Reviews and Meta-Analyses Extension for Scoping Reviews (PRISMA-ScR) standards were implemented in the narrative review. The 16 relevant publications were obtained, and four forms of outdoor play were identified: (1) physical play, (2) constructive play, (3) imaginative play, and (4) games with rules. When all four types were examined further, the findings were synthesised into a literature matrix and incorporated as supporting statements. According to the systematic narrative review, all four forms of outdoor play are beneficial to children’s well-being and may coexist during playtime.